2 - Revisiting the Postmodern Condition of a Higher Education Landscape: South Africa’s Higher Education Epochal Archive, 1999–2002 - Mashige, Mashudu Churchill; Chaka, Chaka (Journal of Higher Education in Africa, 2022)
This article problematizes and critiques the change scenario which unfolded in the South African higher education (HE) landscape over the period 1999–2002. It locates its discussion and analysis within an ideo-critical discourse-interpretive analytics framework. It also employs the following conceptual tools: chaos theory; liminality; negative knowledge; manageri- alism and corporatism; marketization and technologization of discourses; and postmodernity and globalization. Against this backdrop, the article first argues that the change scenario, which occurred in some of South Africa’s higher education institutions (HEIs) during this period, was predicated on the aforesaid conceptual devices. Second, it contends that most of South Africa’s HEIs during that historical juncture were being inveigled into a postmodern condition, even though they were still epicentres of academic modernity. In the light of all this, the article counter-argues that the post- modern intervention in the HE system as driven by the state only served to worsen the difficulties faced by many of the then historically disadvantaged institutions (HDIs) which were part of this system. Finally, the article ends by offering some of the prospects that were in the offing for South Africa’s HEIs at that time.